2020
DOI: 10.1007/s00330-020-07340-4
|View full text |Cite
|
Sign up to set email alerts
|

Survival among women diagnosed with screen-detected or interval breast cancer classified as true, minimal signs, or missed through an informed radiological review

Abstract: Objectives “True” breast cancers, defined as not being visible on prior screening mammograms, are expected to be more aggressive than “missed” cancers, which are visible in retrospect. However, the evidence to support this hypothesis is limited. We compared the risk of death from any cause for women with true, minimal signs, and missed invasive screen-detected (SDC) and interval breast cancers (IC). Methods This nation-wide study included 1022 SDC and 788 IC diagnosed through BreastScreen Norway during 2005–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Further, studies have identified genetic or molecular differences between the screen-detected and interval cancer, though these differences have been less marked or disappeared after adjusting for confounders as age, mammographic density and histologic type and grade (192,213,214). The worse survival for interval cancer persists even after adjustment for histopathological tumor characteristics (195,196,215,216). Thus, to improve detection of "killing cancers" and hence the mortality rates from breast cancer, a focus on reduction of interval cancer rates seems reasonable.…”
Section: Screen-detected Versus Interval Cancermentioning
confidence: 99%
“…Further, studies have identified genetic or molecular differences between the screen-detected and interval cancer, though these differences have been less marked or disappeared after adjusting for confounders as age, mammographic density and histologic type and grade (192,213,214). The worse survival for interval cancer persists even after adjustment for histopathological tumor characteristics (195,196,215,216). Thus, to improve detection of "killing cancers" and hence the mortality rates from breast cancer, a focus on reduction of interval cancer rates seems reasonable.…”
Section: Screen-detected Versus Interval Cancermentioning
confidence: 99%
“… 5 , 13 , 34 , 35 However, recent studies have not reported differences in long-term survival between SBCs and IBCs. 36 One study reported that except for the slightly larger size of IBC, the tumor characteristics of SBC and IBC were comparable. 37 Because our population-based screening study could not compare the tumor characteristics of IBC and SBC, further hospital-based studies with available tumor information should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for lower survival rates of IBC (<1 year) compared with SBC have been suggested to be greater tumor size, more aggressive nature (eg, more lymph node involvement), and a higher proportion of lobular histologic characteristics . However, recent studies have not reported differences in long-term survival between SBCs and IBCs . One study reported that except for the slightly larger size of IBC, the tumor characteristics of SBC and IBC were comparable .…”
Section: Discussionmentioning
confidence: 99%
“…Parametric models can be used to correct for lead time bias (Abrahamsson et al., 2020; Chen et al., 2012; Duffy et al., 2008; Lee et al., 2018; Mahnken et al., 2008; Walter & Stitt, 1987; Wu et al., 2007) and to reduce length time bias (Chen et al., 2012; Cucchetti et al., 2016; Hofvind et al., 2016; Mahnken et al., 2008). Some authors tried to reduce length time bias by using other control groups (Allgood et al., 2011; Kalager et al., 2009; Lawrence et al., 2009; Tsuruda et al., 2021; Walter & Stitt, 1987). However, to our knowledge, no existing approach can fully avoid the three biases.…”
Section: Introductionmentioning
confidence: 99%